Prosaposin/Saposin Expression in the Developing Rat Olfactory and Vomeronasal Epithelia - Kai Kitamura; Kyoko Saito; Takeshi Homma; Aimi Fuyuki; Sawa Onouchi; Shouichiro Saito (Journal of Developmental Biology)
Prosaposin is a glycoprotein widely conserved in vertebrates, and it acts as a precursor for saposins that accelerate hydrolysis in lysosomes or acts as a neurotrophic factor without being processed into saposins. Neurogenesis in the olfactory neuroepithelia, including the olfactory epithelium (OE) and the vomeronasal epithelium (VNE), is known to occur throughout an animal’s life, and mature olfactory neurons (ORNs) and vomeronasal receptor neurons (VRNs) have recently been revealed to express prosaposin in the adult olfactory organ. In this study, the expression of prosaposin in the rat olfactory organ during postnatal development was examined. In the OE, prosaposin immunoreactivity was observed in mature ORNs labeled using olfactory marker protein (OMP) from postnatal day (P) 0. Immature ORNs showed no prosaposin immunoreactivity throughout the examined period. In the VNE, OMP-positive VRNs were mainly observed in the basal region of the VNE on P10 and showed an adult-like distribution from P20. On the other hand, prosaposin immunoreactivity was observed in VRNs from P0, suggesting that not only mature VRNs but also immature VRNs express prosaposin. This study raises the possibility that prosaposin is required for the normal development of the olfactory organ and has different roles in the OE and the VNE.